Analisis atas Kinerja Finansial Klub Sepak Bola Profesional Bali United FC dengan Pendekatan Accounting-Based dan Market-Based Measure - Widodo, Heri; Agustin, Kirani Safitri (Kompartemen : Jurnal Ilmiah Akuntansi, 2025)
This research focuses on the Financial Performance Analysis of Bali United FC Professional Football Club with an Accounting Based Measure and Market Based Measure approach with quantitative descriptive methods. This research uses secondary data. The purpose of this study is to analyze the main financial components and assess their financial performance. Based on the results of the study, the financial components that affect the business continuity of Bali United FC football club are Revenue and Intangible Assets form player registration. While the analysis of Bali United FC's financial ratios for the period 2019 to 2022 is based on Accounting Based Measure, it can be said that this football club experienced several fluctuations in financial performance. Meanwhile, Bali United FC's financial performance based on analysis using the Market Based Measure approach shows mostly positive financial performance. This is because Bali United FC's Thobin's Q value has a Q > 1 value.